Hubungan Pengetahuan Ibu Menyusui Dengan Pemberian Kolostrum Di Wilayah Kerja Puskesmas Pargarutan Tapanuli Selatan Tahun 2023 - Masrelawani Masrelawani; Erin Padilla Siregar (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2023)
Abortion can endanger the mother's health because it can cause bleeding, uterine perforation, infection and shock. Bleeding occurs due to not yet releasing all the products of conception from the endometrial wall, so that the blood vessels are always open to empty the uterus of the remaining products of conception. The next consequence of abortion is perforation, perforation occurs when scraping/curettage, if this happens it is necessary to carry out a laparotomy according to the extent of the perforation. Infection can occur due to the accumulation of dead and rotting products of conception in the body, causing infection, shock, can occur in cases of abortion due to severe infection or profuse bleeding. The incidence of abortion in Indonesia in 2012 was 4%. The aim is to determine the relationship between gestational age and distance with the incidence of abortion in 2023. termination of the pregnancy process before the gestational age is less than 28 weeks (Manuaba, 2010). Abortion is the ending of a pregnancy through any means, spontaneous or artificial, before the fetus is able to survive with limitations based on gestational age and body weight. This research is an observational analytical research with a research design control cases. The samples taken to support this research were all abortion patients at the Pargarutan Health Center, South Tapanuli, totaling 30 people.